Feasibility of a Guided Self-Help Intervention to Reduce Psychological Distress in South Sudanese Refugee Women in Uganda - Tol A. Wietse, Jura Augustinavicius, Leku R. Marx, Adaku Alex, Mark van Ommeren (World Psychiatry, 2018)
Implementing evidence-based psychological interventions in low-resource refugee settings is challenging, because of the need for an extensive workforce of trainers, supervisors and facilitators1,2. Self-Help Plus (SH1) was developed by the World Health Organization (WHO) as a tool potentially applicable in those settings. SH1 is a guided self-help intervention consisting of five audio-recorded sessions and an illustrated self-help manual. It can be provided to large groups (20 to 30 participants) and facilitated by lay helpers with minimal training. It aims to reduce psychological distress in people with a range of common mental disorders and subthreshold symptoms. It is based on acceptance and commitment therapy, a third wave cognitive behavioral therapy focused on enhancing psychological flexibility.